KRAS (but not BRAF) mutations in ovarian serous borderline tumor are associated with recurrent low-grade serous carcinoma - Tsang, Yvonne T. (2013)
BRAF and KRAS mutations in ovarian serous borderline tumors (OSBTs) and ovarian low-grade serous carcinomas (LGSCs) have been previously described. However, whether those OSBTs would progress to LGSCs or those LGSCs were developed from OSBT precursors in previous studies is unknown. Therefore, we assessed KRAS and BRAF mutations in tumor samples from 23 recurrent LGSC patients with known initial diagnosis of OSBT. Paraffin blocks from both OSBT and LGSC samples were available for 5 patients, and either OSBT or LGSC were available for another 18 patients. Tumor cells from paraffin-embedded tissues were dissected out for mutation analysis by conventional polymerase chain reaction (PCR) and Sanger sequencing. Tumors that appeared to have wild-type KRAS by conventional PCR–Sanger sequencing were further analyzed by full COLD (coamplification at lower denaturation temperature)-PCR and deep sequencing. Full COLD-PCR was able to enrich the amplification of mutated alleles. Deep sequencing was performed with the Ion Torrent personal genome machine (PGM). By conventional PCR–Sanger sequencing, BRAF mutation was detected only in one patient and KRAS mutations were detected in 10 patients. Full COLD-PCR deep sequencing detected low-abundance KRAS mutations in eight additional patients. Three of the five patients with both OSBT and LGSC samples available had the same KRAS mutations detected in both OSBT and LGSC samples. The remaining two patients had only KRAS mutations detected in their LGSC samples. For patients with either OSBT or LGSC samples available, KRAS mutations were detected in 7 OSBT samples and 6 LGSC samples. To our surprise, patients with the KRAS G12V mutation appeared to have shorter survival times. In summary, KRAS mutations are very common in recurrent LGSC, while BRAF mutations are rare. The findings indicate that recurrent LGSC can arise from proliferation of OSBT tumor cells with or without detectable KRAS mutations.